Antagonistic effects of Chaetomium globosum and Trichoderma viride against Chili Anthracnose - P. Rohaendi; Sigit Sudjatmiko; Tunjung Pamekas; K. Soytong; J. J. Song; D. W. Ganefianti; Hendri Bustamam; Mimi Sutrawati (International Journal of Agricultural Technology, 2026)
The research demonstrated that Trichoderma viride and Chaetomium globosum inhibited Colletotrichum acutatum by 90.30% and 88.20%, respectively, primarily via competition for nutrients/space and parasitism, with no observed antibiosis. the field trials revealed that both fungi significantly reduced anthracnose severity. Trichoderma viride applications at 1, 2, and 3 g/L decreased disease incidence by 80.68%, 91.16%, and 92.27%, respectively, while Chaetomium globosum reduced it by 87.61–92.65%. Both exceeded synthetic fungicide Antracol (83.48–89.37% reduction) as a controlled treatment. Attack intensity followed a similar trend, with Trichoderma viride (95.12–97.46% suppression) and Chaetomium globosum (92.76–96.83%) surpassing Antracol (89.95–93.80%). Additionally, Trichoderma viride and Chaetomium globosum enhanced salicylic acid levels in chili plants, suggesting induced systemic resistance. These findings highlighted the potential of antagonistic fungi as sustainable biocontrol agents which would develop to be biofungicide, offering effective anthracnose management while reducing chemical residues.
Keywords: Plant-Microbe Interactions and Immunity; Plant Pathogens and Fungal Diseases; Plant Pathogens and Resistance